2005
DOI: 10.1186/1477-7827-3-47
|View full text |Cite
|
Sign up to set email alerts
|

Calcium alginate microencapsulation of ovarian follicles impacts FSH delivery and follicle morphology

Abstract: Background: We have previously shown that suspension culture prevents follicle flattening and maintains three-dimensional follicle architecture better than culture on flat plates. However, many of the follicles cultured in suspension do eventually rupture, as basement membrane integrity is lost and the three-dimensional structure of the follicle is altered. Therefore, the objective of this study is to support three-dimensional follicle architecture during in vitro growth of ovarian follicles through encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Furthermore, its flexibility can accommodate cell proliferation, but its rigidity prevents dissociation of the 3-dimensional follicular unit. The rigidity of the alginate capsule affects follicle development as inhibition of growth and reduced steroidogenesis have been reported in murine follicles embedded in 1% alginate gels (62) whereas fully grown human (29) and macaque (27,28,30) oocytes have been produced using 0.5% and 0.25% gels, respectively. Indeed, a more rigid environment of 2% alginate supported macaque primordial follicle growth in vitro (42).…”
Section: Early Follicle Development In Vitromentioning
confidence: 99%
“…Furthermore, its flexibility can accommodate cell proliferation, but its rigidity prevents dissociation of the 3-dimensional follicular unit. The rigidity of the alginate capsule affects follicle development as inhibition of growth and reduced steroidogenesis have been reported in murine follicles embedded in 1% alginate gels (62) whereas fully grown human (29) and macaque (27,28,30) oocytes have been produced using 0.5% and 0.25% gels, respectively. Indeed, a more rigid environment of 2% alginate supported macaque primordial follicle growth in vitro (42).…”
Section: Early Follicle Development In Vitromentioning
confidence: 99%
“…Encapsulation methods using hydrogels such as alginate have been applied to the in vitro culture of various tissues (Butcher and Nerem 2004;Azab et al 2006;Eyrich et al 2007), including ovarian follicles (Pangas et al 2003;Kreeger et al 2005;Xu et al 2006b). Alginate is a natural biopolymer extracted from brown algae and its absence of bioactivity, intrinsic biocompatibility and capacity for forming a gel with well-defined features have made it particularly useful for in vitro follicle culture (Heise et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They found that cells were viable and spread in both 2% alginate and 0.5% in alginate-RGD (arginine-glycine-aspartic acid peptide-contains cell adhesion ligands) hydrogels during 6 days. Once alginate derived from natural source, it exhibits an inherent biocompatibility [37] and is also physicochemically well defined to provide a stable culture system without interfere with cellular functions [25,38]. Alginate matrix modulates and supports several biological processes, including the transport of bioactive agents, such as growth factors and hormones [32,33].…”
Section: Discussionmentioning
confidence: 99%